1989
DOI: 10.3102/00028312026003422
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Quality of Academic Advising: The Effect on Freshman Attrition

Abstract: Using data from 1,033 freshmen at a public urban university, this study examined the effect of the perceived quality of academic advising on student attrition in a model of the student attrition process. High-quality advising negatively influenced attrition through effects on GPA, satisfaction in the role of a student, the value of a college education for future employment, and intent to leave the university. Low-quality advising was related to greater attrition than was high-quality advising, but, on the othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
66
1
1

Year Published

1995
1995
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(71 citation statements)
references
References 38 publications
3
66
1
1
Order By: Relevance
“…The work by Metzner (1989) did not find any direct relationship between academic advising and retention.…”
Section: Studies Claiming Direct Associations Between Advising and Rementioning
confidence: 96%
See 3 more Smart Citations
“…The work by Metzner (1989) did not find any direct relationship between academic advising and retention.…”
Section: Studies Claiming Direct Associations Between Advising and Rementioning
confidence: 96%
“…Miller's approach also presents a structure that is more functional for use in individualized institutional assessment of learning outcomes, particularly regarding the "efficiency" of a particular advising model for a particular student population. While Miller's (in press) four dimensional focus on advising structures provides a framework for assessment, it is lacking a variable that has been identified in the literature as a key to student retention and advising learning outcomes; that factor is the frequency with which a student sees an academic advisor (Astin, 1977;Beal & Noel, 1980;Lowe & Toney, 2000;Metzner, 1989;Pascarella & Terenzini, 1977;. Some institutions do not require any of their students to ever see an academic advisor, while other institutions may require that a student meet with an academic advisor several times throughout the year.…”
Section: Background Of the Problemmentioning
confidence: 99%
See 2 more Smart Citations
“…Through these interactions, professionals and faculty members at the institution can leverage the opportunity to address the complexities of new student transitions, academic and career exploration, and student cognitive and social development. Research has shown that academic advising can improve college student academic and social success, college experience satisfaction, gradepoint average (GPA), learning, retention, and graduation rates in the United States (Abdussalam, Chen, & Khan, 2007;Bahr, 2008;Drake, 2011;Gardiner, 1994;Hale, Graham, & Johnson, 2009;Heisserer & Parette, 2002;Kiker, 2008;Kuh, 2008;Ludwig-Hardman & Dunlap, 2003;Metzner, 1989;Pan, Guo, Alikonis, & Bai, 2008;Rice et al, 2009;Schwebel, Walburn, Jacobsen, Jerrolds, & Klyce, 2008;Smith & Allen, 2006). However, the role of academic advising in non-Western settings has escaped scrutiny.…”
mentioning
confidence: 99%